Operational Risk Management Design of General Reinsurance Facultative Administration PT. XYZ - Christi Vidya Mahacintya; Nur Hasanah; Widodo Ramadyanto (Jurnal Aplikasi Bisnis dan Manajemen, 2025)
Background: The facultative administration of general reinsurance of PT. XYZ has experienced several operational risks, such as scattered and incomplete bargaining documents between companies and emails from insurance companies that were not promptly responded to. However, in practice, the facultative administration of general reinsurance of PT. XYZ has not implemented operational risk management.Purpose: The purpose of this study is to identify operational risks and their causes, analyze the priority level of handling, and recommend handling operational risks. Design/methodology/approach: This research was conducted from November 2023 to January 2024 and required 9 respondents. Furthermore, the information received based on the respondents' statements will be processed using Fishbone Diagram, FMEA (Failure Mode and Effect Analysis), and Pareto Diagram methods.Finding/Results: 11 risk sources were identified and grouped into process, human, system, and external risk categories, of which 3 were prioritized for handling, namely the risk that emails related to offers from insurance companies were not responded on time, an error occurred on the company's website database, and the information in the business offer slip did not explain in detail the coverage value of each risk to be reinsured. Conclusion: Some of the handling efforts proposed in this study include adding competent human resources, carrying out regular system maintenance, and providing reminders to insurance companies.Originality/value (State of the art): The facultative administration of general reinsurance of PT XYZ does not escape the existence of several operational risks that fall into the categories of process, human, system and external risks. Keywords: facultative administration, FMEA, operational risk, Pareto diagram, risk priority